Huanglongmycin A-C, Cytotoxic Polyketides Biosynthesized by a Putative Type II Polyketide Synthase From Streptomyces sp. CB09001 - Jiang, Lin; Pu, Hong; Xiang, Jingxi; Su, Meng; Yan, Xiaohui; Yang, Dong; Zhu, Xiangcheng; Shen, Ben; Duan, Yanwen; Huang, Yong (Frontiers in Chemistry, 2018)
Three natural products of nonaketide biosynthetic origin, probably biosynthesized from nine molecules of malonyl-CoA, have been isolated. Herein we described the isolation and structure elucidation of huanglongmycin (HLM) A-C and identification of the putative hlm biosynthetic gene cluster from Streptomyces sp. CB09001, isolated from a karstic cave in Xiangxi, China. Albeit previously isolated, HLM A was reported for the first time to exhibit moderate cytotoxicity against A549 lung cancer cell line (IC50 = 13.8 ± 1.5 μM) and weak antibacterial activity against gram-negative clinical isolates. A putative biosynthetic pathway for HLM A, featuring a nonaketide-specific type II polyketide synthase, was proposed. It would be consistent with the isolation of HLM B and C, which are two new natural products and likely shunt metabolites during HLM A biosynthesis.